The Links Between Community-Based Financial Inclusion and Household Food Availability: Evidence from Mozambique - Aweke Tadesse; Kenan Li; Jesse Helton; Jin Huang; David Ansong (Foods)
Financial inclusion can boost wealth, health, and quality of life. However, few studies have examined how women’s participation in community-based financial inclusion opportunities, such as village saving and loan groups (VSLGs), relates to household food security. Using program data from central Mozambique, this study examined whether low-income women’s participation in VSLGs directly increases household food availability, as well as indirectly through increased asset ownership. Employing a post-test-only comparison group quasi-experimental design, the study sampled 205 female VSLG participants and non-participants from three sub-villages in Mozambique’s Sofala province. Structural equation modeling (SEM) results indicated that low-income women’s participation in VSLGs is directly associated with a reduction in household hunger score (β = −0.21, p < 0.01), as well as indirectly associated through the mediating role of household assets ([Sobel indirect effect] = −0.06, p = 0.05). The VSLG participants showed a significant increase in household asset ownership compared to non-VSLG participants (β = 0.15, p < 0.05). Further, increased asset ownership significantly correlated with a lower probability of household hunger (β = −0.30, p < 0.01). The results suggest that community-based financial inclusion approaches could improve the availability of food through asset building among Mozambique’s low-income women. The study offers a potential strategy for policymakers and development experts to utilize community approaches to financial inclusion to improve rural and low-income women’s livelihoods.